1995
DOI: 10.1074/jbc.270.27.16409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tuberin, the Tuberous Sclerosis-2 Product. TUBERIN POSSESSES SPECIFIC Rap1GAP ACTIVITY

Abstract: Tuberous sclerosis (TSC) is a human genetic syndrome characterized by the development of benign tumors in a variety of tissues, as well as rare malignancies. Two different genetic loci have been implicated in TSC; one of these loci, the tuberous sclerosis-2 gene (TSC2), encodes an open reading frame with a putative protein product of 1784 amino acids. The putative TSC2 product (tuberin) contains a region of limited homology to the catalytic domain of Rap1GAP. We have generated antisera against the N-terminal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
215
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(225 citation statements)
references
References 31 publications
6
215
1
3
Order By: Relevance
“…Surprisingly, in spite of the 70% homology of Rap1 and Rap2 (Bokoch, 1993), C3G-CD does not react with Rap2A (Table 1) and only very weakly with Rap2B ( Figure 3; Table 1). A similar discrimination in favour of Rap1 over Rap2 has been reported for two di erent RapGAPs (Rubin®eld et al, 1991;Wienecke et al, 1995). These ®ndings suggest that Rap2 proteins most likely have their own regulatory proteins and their identification might help elucidating the biological function of Rap2.…”
Section: Resultssupporting
confidence: 73%
“…Surprisingly, in spite of the 70% homology of Rap1 and Rap2 (Bokoch, 1993), C3G-CD does not react with Rap2A (Table 1) and only very weakly with Rap2B ( Figure 3; Table 1). A similar discrimination in favour of Rap1 over Rap2 has been reported for two di erent RapGAPs (Rubin®eld et al, 1991;Wienecke et al, 1995). These ®ndings suggest that Rap2 proteins most likely have their own regulatory proteins and their identification might help elucidating the biological function of Rap2.…”
Section: Resultssupporting
confidence: 73%
“…1993). It has been shown that tuberin, like Rap1GAP, possesses in vitro GAP activity for Rap1 (Wienecke et al, 1995). Rap1 is a member of the superfamily of Ras-related proteins, which are active when bound to GTP and inactive when bound to GDP (Lowy and Willumsen, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the TSC2 gene have been described in patients with TSC (Kumar et al, 1995;Wilson et al, 1996) and loss of heterozygosity at the TSC2 locus has been demonstrated in TSC patient lesions, as well as in sporadic tumours of non-TSC patients (Green et al, 1994;Henske et al, 1995;Carbonara et al, 1996). The TSC2-encoded protein, designated tuberin, functions as a GTPase accelerating protein (GAP) for the small molecular weight GTPases Rap1a and Rab5 (Wienecke et al, 1995Xiao et al, 1997). Very recently, we have shown that the absence of tuberin can induce quiescent Go-arrested cells to re-enter the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The two proteins interact through coiled-coil domains to form a stable, functional heterodimer (van Slegtenhorst et al, 1998). The C-terminal region of TSC2 shows homology to the Rap GTPase activating protein, and GTPase activating protein activity to various G-proteins (Wienecke et al, 1995;Xiao et al, 1997 NUAK1, NUAK2 SIK1, SIK2 QSK MARK1, MARK2, MARK3, MARK4 BRSK1, BRSK2 SNRK inactive active p la s m a m e m b r a n e Figure 1 Activation and translocation of LKB1. LKB1 is activated by its translocation from the nucleus to the cytoplasm.…”
Section: Regulation Of the Tsc1:tsc2 Complexmentioning
confidence: 99%